2023
DOI: 10.1186/s12950-023-00358-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards clinical application of GlycA and GlycB for early detection of inflammation associated with (pre)diabetes and cardiovascular disease: recent evidence and updates

Erik Fung,
Eunice Y. S. Chan,
Kwan Hung Ng
et al.

Abstract: Summary Cardiometabolic diseases are associated with low-grade inflammation early in life and persists into old age. The long latency period presents opportunities for early detection, lifestyle modification and intervention. However, the performance of conventional biomarker assays to detect low-grade inflammation has been variable, particularly for early-stage cardiometabolic disorder including prediabetes and subclinical atherosclerotic vascular inflammation. During the last decade, the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…For the RE group, lipid and lipoprotein profiles may be indicating a divergent systemic response to injury and an underlying lipid-mediated inflammatory mechanism compared to the DRE group (Figure 2, Figure 4). GlycB is a composite signal from the 5-N-acetyl methyl groups of sialic acid in glycosylated acute phase protein markers during inflammation [58]. GlycB and CRP can correlate [58] but numerous studies have identified that the two markers can reflect different inflammatory processes [59], as seen in conditions such as obesity [60], type 2 diabetes [61] and cardiovascular disease [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the RE group, lipid and lipoprotein profiles may be indicating a divergent systemic response to injury and an underlying lipid-mediated inflammatory mechanism compared to the DRE group (Figure 2, Figure 4). GlycB is a composite signal from the 5-N-acetyl methyl groups of sialic acid in glycosylated acute phase protein markers during inflammation [58]. GlycB and CRP can correlate [58] but numerous studies have identified that the two markers can reflect different inflammatory processes [59], as seen in conditions such as obesity [60], type 2 diabetes [61] and cardiovascular disease [59].…”
Section: Discussionmentioning
confidence: 99%
“…GlycB is a composite signal from the 5-N-acetyl methyl groups of sialic acid in glycosylated acute phase protein markers during inflammation [58]. GlycB and CRP can correlate [58] but numerous studies have identified that the two markers can reflect different inflammatory processes [59], as seen in conditions such as obesity [60], type 2 diabetes [61] and cardiovascular disease [59]. With the difference observed in GlycB and CRP levels (though not statistically significant) between RE and DRE (Figure S3) two differing inflammatory patterns may have triggered in response to the burn injury.…”
Section: Discussionmentioning
confidence: 99%